2022
DOI: 10.1177/01655515221124003
|View full text |Cite
|
Sign up to set email alerts
|

Agency and liminality during the COVID-19 pandemic: Why information literacy cannot fix vaccine hesitancy

Abstract: This article employs a sociological and dialogical information perspective to identify what shape information literacy practice takes for people who are hesitant about the COVID-19 vaccine. An information perspective places information and people’s relations with information at the centre of the inquiry. The study carried out 14 semi-structured interviews with UK adults who had not yet received or taken up their invitation to have the COVID-19 vaccine. Outcomes of this study suggest that information literacy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Although the Covid-19 vaccine safely prevents Covid-19, people still refused it (Kafadar, 2022;Ouyang, 2022). Hicks and Lloyd (2022) argued that although information literacy is useful, it did not prevent vaccine hesitancy in adults. Specifically, they found that people who were informationally literate preferred to wait until they had more information about potentially negative side effects.…”
Section: Information Literacy During the Covid-19 Pandemicmentioning
confidence: 99%
“…Although the Covid-19 vaccine safely prevents Covid-19, people still refused it (Kafadar, 2022;Ouyang, 2022). Hicks and Lloyd (2022) argued that although information literacy is useful, it did not prevent vaccine hesitancy in adults. Specifically, they found that people who were informationally literate preferred to wait until they had more information about potentially negative side effects.…”
Section: Information Literacy During the Covid-19 Pandemicmentioning
confidence: 99%
“…The historical trajectory of VH traverses many vaccine-recommended diseases, and vaccine skeptics have been present since the smallpox vaccination exercise carried out in the 19th century [17][18][19][20][21]. However, the phenomenon of VH has been magnified in the technological advancement era of the internet and social media, with exponential communications and interaction strategies and platforms globally [17,20,[22][23][24][25]. As studies consistently point out, VH and the underutilization of accessible vaccination services contribute to the continued and/or increasing burden of diseases from vaccine-preventable diseases (VPDs) around the world, which stymies decades of public health efforts and desired progress [11,[26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The study reported here forms part of a broader research project examining how information literacy and information practices unfolded during the COVID-19 pandemic. Previous phases have explored the initial COVID-19 lockdown as well as hesitation in relation to the COVID-19 vaccine (Lloyd and Hicks, 2020, 2021Hicks and Lloyd, 2022). Phase Three of this project, which forms the subject of this paper, focusses on the impact of COVID-19 on the workplace and, in particular, the role that digital technologies play in enabling or constraining information literacy practices necessary for the operationalisation of work.…”
Section: Introductionmentioning
confidence: 99%